Maternal health care utilization in Nairobi and Ouagadougou: evidence from HDSS - Clémentine Rossier; Kanyiva Muindi; Abdramane Soura; Blessing Mberu; Bruno Lankoande; Caroline Kabiru; Roch Millogo (Taylor & Francis Group, 2014)
Background: Maternal mortality is higher and skilled attendance at delivery is lower in the slums of Nairobi (Kenya) compared to Ouagadougou (Burkina Faso). Lower numbers of public health facilities, greater distance to facilities, and higher costs of maternal health services in Nairobi could explain these differences. Objective: By comparing the use of maternal health care services among women with similar characteristics in the two cities, we will produce a more nuanced picture of the contextual factors at play. Design: We use birth statistics collected between 2009 and 2011 in all households living in several poor neighborhoods followed by the Nairobi and the Ouagadougou Health and Demographic Surveillances Systems (n=3,346 and 4,239 births). We compare the socioeconomic characteristics associated with antenatal care (ANC) use and deliveries at health facilities, controlling for demographic variables. Results: ANC use is greater in Nairobi than in Ouagadougou for every category of women. In Ouagadougou, there are few differentials in having at least one ANC visit and in delivering at a health facility; however, differences are observed for completing all four ANC visits. In Nairobi, less-educated, poorer, non-Kikuyu women, and women living in the neighborhood farther from public health services have poorer ANC and deliver more often outside of a health facility. Conclusions: These results suggest that women are more aware of the importance of ANC utilization in Nairobi compared to Ouagadougou. The presence of numerous for-profit health facilities within slums in Nairobi may also help women have all four ANC visits, although the services received may be of substandard quality. In Ouagadougou, the lack of socioeconomic differentials in having at least one ANC visit and in delivering at a health facility suggests that these practices stem from the application of well-enforced maternal health regulations; however, these regulations do not cover the entire set of four ANC visits.